2003
DOI: 10.1118/1.1621135
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic photon transport calculations in general geometry for external beam radiation therapy

Abstract: A deterministic method is described for performing three-dimensional (3D) photon transport calculations of a LINAC head and phantom/patient geometry to obtain dose distributions for therapy planning. The space, energy, and directional-dependent photon flux density is obtained by numerically solving the Boltzmann equation in general 3D geometry using the method of characteristics. The deterministic transport calculations use similar ray tracing routines as found in Monte Carlo (MC) codes. A special treatment is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In addition, the deterministic method has the highest computational efficiency among the three methodologies. Although deterministic photon dose estimation has been widely used in the field of radiation therapy 28 32 , its use has not been fully investigated for CT imaging. Because CT imaging is fundamentally different from radiation therapy, in terms of X-ray photon energy, interaction mechanisms, beam shape, and source trajectory, a CT-specific approach to deterministic photon dose calculation is required.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the deterministic method has the highest computational efficiency among the three methodologies. Although deterministic photon dose estimation has been widely used in the field of radiation therapy 28 32 , its use has not been fully investigated for CT imaging. Because CT imaging is fundamentally different from radiation therapy, in terms of X-ray photon energy, interaction mechanisms, beam shape, and source trajectory, a CT-specific approach to deterministic photon dose calculation is required.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a third physical quantity was required to calculate the delivered dose: the local particle fluence. For this, a simple deterministic approximation was used, incorporating the inverse‐square law and exponential decay in accordance with the attenuation of the beam in water 17 . Equation gives the first order (uncollided) angularly independent fluence approximation at r if the accelerator target is represented by a point source at location r0.…”
Section: Methodsmentioning
confidence: 99%
“…For this, a simple deterministic approximation was used, incorporating the inverse-square law and exponential decay in accordance with the attenuation of the beam in water. 17 Equation (1) gives the first order (uncollided) angularly independent fluence approximation at r if the accelerator target is represented by a point source at location r 0 . Exponential decay resulting from the attenuation of the material is dictated by the optical distance τ (the mean free path length of water) and Q A ðr 0 , EÞ is the energy dependent photon source intensity at r 0 .…”
Section: B Data Channelsmentioning
confidence: 99%
“…For applications in medical physics, it apparently does not take advantage of the well-defined pixel geometry, basically a three-dimensional cuboid array. The TRANSMED code 6 , on the other hand, uses the structured orthogonal mesh and solves the integral form of the transport equation on the discrete direction lines by the method of characteristics ͑MOC͒. Multistep collision sources are employed in which a sequential equation of the uncollided, the first-collision, the second-collision, and collided sources are solved.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have reported their external beam radiotherapy calculations based on deterministic transport equations. [6][7][8][9] Williams et al 6 have described a deterministic method based on the BTE to perform three-dimensional photon transport calculations of a LINAC head and phantom or patient geometry using the TRANSMED code. The method of characteristics was used for integration of the transport equation and the angular flux was decomposed into multistep collision flux, such as the uncollided, first-collision, second-collision and collided flux.…”
Section: Introductionmentioning
confidence: 99%